Remote Work and Productivity: Analyzing the Mediating Effect of Work-Life Balance - Ghalan, Usham; Shrestha, Sneha; Thapa, Swastika; Bhatta, Sushant; KC, Sushan; Ghimire, Sujal; Parajuli, Suman Kamal (International Journal of Education, Management, and Technology, 2025)
This study explores the relationship between remote work, employee productivity, and work-life balance, with a specific focus on the mediating role of work-life balance. Given the rise of remote work in various sectors, particularly in the IT industry, it becomes crucial to understand how remote work influences employee productivity and how work-life balance may play a central role in this relationship. A quantitative, cross-sectional design was used, surveying 110 IT professionals from Kathmandu Valley, Nepal. A pre-tested Likert scale questionnaire collected data, measuring variables such as work-life balance, employee productivity, and remote work. Descriptive analysis revealed that most respondents worked remotely (42.7%) or in a hybrid setup (37.3%). While the mean score for work-life balance (3.45) suggested a generally positive perception of remote work's role in balancing personal and professional lives, challenges like difficulty disconnecting and burnout were noted. Employee productivity ratings highlighted that work-life balance positively impacted productivity (mean = 3.83). The remote work factor demonstrated moderate satisfaction with tools, communication, and goal clarity but indicated areas for improvement, especially in technical support (mean for remote work = 3.55). Correlation analysis showed strong positive relationships between work-life balance, remote work, and employee productivity (p < 0.01). The study concludes that work-life balance acts as a key mediator between remote work and productivity, underscoring its importance in fostering an efficient remote working environment. Though employees report a generally positive view of remote work’s ability to provide flexibility, issues with communication and technical support may hinder overall productivity. Thus, improving these areas could maximize remote work's benefits.